EFEITO NEUROPROTETOR E COMPORTAMENTAL DO Hypericum perforatum EM UM MODELO ANIMAL DE DOENÇA DE PARKINSON - Vecchia, Débora Dalla (2013)
The objective of this study was to test the potential neuroprotective action of Hypericum perforatum alcoholic extract on dopaminergic neurons lesioned in rat by the toxin 6-hydroxydopamine (6-OHDA) as an animal model of PD. The 6-OHDA was stereotaxically infused in rats into the medial forebrain bundle unilaterally to test rotational behavior and bilaterally to other tests. Hypericum perforatum was administered at doses of 100, 200 and 400 mg/kg by gavage for 35 days, starting 28 days before the treatment of the lesion. In the test of rotational behavior, a unilateral lesion with 6-OHDA caused an increase in the number of contralateral rotations and this effect was reversed by treatment with Hypericum perforatum. In the sucrose preference test was significant reduction in depressive-like behavior in animals injured with 6-OHDA-treated and Hypericum perforatum. In the forced swimming test, 6-OHDA animals treated with Hypericum perforatum kept less time immobile when compared to 6-OHDA animals treated with vehicle. In the open field test, we observed a significant reduction of locomotor function in the injured groups with 6-OHDA, however, according to results obtained in the forced swimming test, the motor impairment did not affect the immobility time. In the social recognition test, animals treated with 6-OHDA Hypericum perforatum performed significantly better than animals treated with 6-OHDA vehicle. In the olfactory discrimination test, there was no difference in the ability to discriminate odors, and possibly did not olfaction loss in animals injured with 6-OHDA. These results suggest that Hypericum perforatum reduced the death of dopaminergic neurons. This potential neuroprotection was confirmed by analysis of Immunodetection of proteins (Western Blot) by expression of the enzyme tyrosine hydroxylase (TH). Together, these results characterize the Hypericum perforatum as a possible drug to be used in the treatment of PD.